Fixation Process With 10% KOH Immersion And Variation Of Heating Temperatures On The Quality Of Pediculus humanus capitis: Proses Fiksasi Dengan Perendaman KOH 10% Dan Variasi Suhu Pemanasan Terhadap Kualitas Sediaan Pediculus humanus capitis - Azizah, Nurul; Mahtuti, Erni Yohani; Faisal (Universitas Muhammadiyah Sidoarjo, 2022)
The preparation of preserved preparations is one of the useful methods to determine the morphology of ectoparasites and insects whose manufacturing process goes through four stages starting with 10% KOH fixation, dehydration process, clearing process, and mounting process. The 10% KOH immersion serves to thin out the chitin layer that forms the exoskeleton, which is a thick covering on the body surface of Pediculus humanus capitis (human lice). The purpose of this study was to determine the quality of the preserved preparations of Pediculus humanus capitis by immersing them in 10% KOH at temperatures of 60°C, 70°C, 80°C, and 90°C for 30 minutes using the whole mount method, in order to observe the entire morphology of the species clearly. The sample used is Pediculus humanus capitis adult stage, as many as 24 tails. Observation of the quality of preserved preparations was assessed based on clarity, color quality, and morphological integrity. At a temperature of 60°C, two good qualities are obtained. Three good qualities are obtained at 70oC. At 80°C, it is of good quality, and at 90°C, there is no good quality. The results of the study were then subjected to statistical tests using the Kruskall-Wallis test, which obtained a p value of 0.040<0.05, so that it could be interpreted that there was an influence of variations in heating temperature and 10% KOH immersion on the quality of Pediculus preserved preparations. humanus capitis. namely, by immersing 10% KOH at 70°C for 30 minutes, with complete morphological characteristics, transparent color, and a clear appearance.